Changes in Ganglion Cell Complex and Peripapillary Retinal Nerve Fiber Layer after Femtosecond Laser-Assisted Cataract Surgery Compared to Manual Phacoemulsification in Patients Receiving a Trifocal Intraocular Lens - Carmen Sánchez-Sánchez; Laureano A. Rementería-Capelo; Virginia Carrillo; Juan Pérez-Lanzac; Inés Contreras (Journal of Ophthalmology)
Introduction. During femtosecond laser-assisted cataract surgery (FLACS), there is a significant increase in intraocular pressure, which might lead to ganglion cell damage. We aimed to determine whether there were differences in the changes produced in the ganglion cell complex (GCC) and peripapillary retinal nerve fiber layer (pRNFL) thickness, as evaluated with optical coherence tomography (OCT), between phacoemulsification and FLACS, after implantation of a trifocal intraocular lens (IOL). Methods. Patients with no coexistent pathologies undergoing cataract surgery with implantation of a PanOptix IOL were explored with the Cirrus-OCT before and three months after surgery. GCC values were obtained from the built-in software. The differences between pre- and postoperative GCC and pRNFL thicknesses after phacoemulsification were compared to differences after FLACS. Results. A total of 171 eyes were included, 74 undergoing FLACS and 97 phacoemulsification. For both groups, there was a statistically significant increase in GCC values after cataract surgery, except for the inferior and inferonasal sectors. There were no statistically significant differences between FLACS and phacoemulsification. Mean change in average GCC and minimum GCC were 1.08 ± 1.40 µm (range −1 to +6 µm) and 1.69 ± 2.54 µm (range −3 to +11 µm) after FLACS and 0.99 ± 1.67 µm (range −5 to +6 µm) and 2.02 ± 3.54 µm (−6 to +18 µm) after phacoemulsification. These values are similar to those previously reported after phacoemulsification with monofocal IOL implantation. No significant changes after surgery were detected for the pRNFL, with no differences between groups. Discussion. There were no differences in the changes produced by FLACS and phacoemulsification in either GCC or pRNFL values. Although mean change was small, the range of variation was wide. Therefore, it is necessary to establish a new baseline for GCC and pRNFL thicknesses after cataract surgery in order to monitor any subsequent changes.